2017
DOI: 10.1590/s2175-97902017000115218
|View full text |Cite
|
Sign up to set email alerts
|

Floating ability and drug release evaluation of gastroretentive microparticles system containing metronidazole obtained by spray drying

Abstract: Gastroretentive floating microparticles were developed and evaluated for the controlled metronidazole delivery for treatment of gastric disease. Floating microparticles, varying in proportions of chitosan and hydroxypropyl methylcellulose or ethylcellulose, were obtained by spray drying. Floating microparticles were characterized by physicochemical and in vitro studies, according to their floating ability and drug delivery. Microparticles presented mean diameter from 1.05 to 2.20 µm. The infrared spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The XRD pattern of pure MLX demonstrates individual intense peaks between the range of 6–30˚ at 2θ of diffraction angle corresponding to 13.17˚, 15.06˚, 18.49˚, and 26.07˚, which demonstrates the crystalline nature of MLX, as shown in Fig 7(A) [ 38 , 70 ]. The HPMC illustrated a wide hump in between the range of 5˚-25˚, which reflects its amorphous state, as displayed in Fig 7(B) [ 74 ]. The XRD pattern of the physical mixture of the MLX as well as HPMC, and optimized formulation (F0) maintained their peaks, which revealed that there was no interaction between the ingredients of the physical mixture and optimized formulation, as depicted in Fig 7(C) and 7(D) [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of pure MLX demonstrates individual intense peaks between the range of 6–30˚ at 2θ of diffraction angle corresponding to 13.17˚, 15.06˚, 18.49˚, and 26.07˚, which demonstrates the crystalline nature of MLX, as shown in Fig 7(A) [ 38 , 70 ]. The HPMC illustrated a wide hump in between the range of 5˚-25˚, which reflects its amorphous state, as displayed in Fig 7(B) [ 74 ]. The XRD pattern of the physical mixture of the MLX as well as HPMC, and optimized formulation (F0) maintained their peaks, which revealed that there was no interaction between the ingredients of the physical mixture and optimized formulation, as depicted in Fig 7(C) and 7(D) [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prepared MTD-SLNs dispersions were centrifuged using a cooling centrifuge (2-16KL, Sigma Laborzentrifugen GmbH, Osterode am Harz, Germany) at 12,000 rpm for 2 h at 4 °C (Badawi et al., 2018 ). The supernatant was collected to measure the free drug concentration using ultraviolet (UV) spectrophotometer (V-630, Jasco, Tokyo, Japan) at 277 nm (Nohemann et al., 2017 ). The entrapment efficiency percent EE% was calculated according to the following equation (Badawi et al., 2018 ): …”
Section: Methodsmentioning
confidence: 99%
“…The precise volume of the samples was withdrawn at regular time intervals till 24 h and replaced with an equal volume of fresh dissolution media. The cumulative release of MTD from lipid nanoparticles was determined spectrophotometrically at 277 nm (Nohemann et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metronidazole is an antibiotic, amebicide, and antiprotozoal used particularly for anaerobic bacteria and protozoa. The unionized metronidazole having the ability to reduce intercellularly, this reduced form covalently binds to DNA, disrupt its helical structure, inhibiting bacterial nucleic acid synthesis and resulting in bacterial cell death 11,12 . Metronidazole widely used for the treatment of H. Pylori eradication therapy, in combination with other antibiotics and one proton pump inhibitor.…”
mentioning
confidence: 99%